Quo Vadis Pengadilan Khusus di Indonesia dalam Batasan Putusan Mahkamah Konstitusi - Bagus Hermanto; Nyoman Mas Aryani (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2023)
In Indonesia, special courts represent a phenomenon of judicial deference which is associated with an independent judicial system and supports the efficient and effective administration of justice. However, the practice in Indonesia shows that there is a need for further discursive research and thinking in the organization of the special justice system in Indonesia, based on internal and external issues in the realization of a special justice order that promotes substantive justice and is based on effectiveness, efficiency, and justice that is based on the needs of legal specificity under the specialized court context. This article utilizes dogmatic legal research based on a statutory approach, a case law approach, and a conceptual approach on a micro-legal research basis to examine the revamping of special courts in Indonesia, including the elaboration of Constitutional Court Decisions relevant to the strengthening of constitutional consolidation in post-reform Indonesia. Furthermore, the findings of this study show that the dynamics of special justice in Indonesia seem to be based on specific needs, international intervention in several cases, and ideas when the 1945 Constitution was amended by strengthening in accordance with conditions and times to achieve substantive justice. Similarly, the failure to build several special courts has become a discourse in recent decades, as various Constitutional Court decisions have directed topics that may be seen in the formation of special courts in the future. These include the existence of electoral and medical courts, which have also emerged as ideas for revamping specialized courts in Indonesia.